ANALISIS PENGENDALIAN INTERN SIKLUS PENDAPATAN PADA PENERBIT ERLANGGA CABANG PALEMBANG - Padriyansyah Padriyansyah; Koefrowi Koefrowi (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
This research is engaged in printing. This printing company before the Covid-19 pandemic was in conditions that generated optimal profits. The occurrence of the Covid-19 pandemic make company profits always decline. This is closely related to the cost behavior and break-even of multiple products in planning short-term profits. The population used in this study is the cost behavior and break-even of multi-products in the short-term profit planner in 2020. The sampling used is purposive sampling. The type and design of the research is descriptive research. Based on the results of the research, the company has not implemented the concept of cost behavior which separates variable costs and fixed costs with the income statement in the multi-product breakeven calculation has not been prepared by variable costing. The conclusion from this study states that companies must apply the concept of cost behavior that separates fixed costs and variable costs. And applying the multi-product breakeven guidelines as a tool in sales revenue for product orders can determine short-term profit.Keywords : Cost Behavior, Multi-Product Break-even, Short-Term Profit     Planning